In-situ transmission electron microscopy for probing the dynamic processes in materials. (20th August 2021) - Zhu, Yuchen; Zhao, Haofei; He, Yang; Wang, Rongming
Abstract: Physic-based materials design often relies on a fundamental understanding on the structure and property relations of materials. By introducing various stimuli into the transmission electron microscope (TEM) sample chamber, in-situ TEM has enabled researchers to carry out experiments directly in the TEM, leading to extensive discoveries on the atomic-scale dynamic processes of materials and crucial mechanistic insights on the origin of material's behaviors such as size-effect in gold catalysis, toughening mechanism of high entropy alloys, and degradation mechanisms of battery materials. The findings have profoundly impacted the materials science and engineering. In this review, we will briefly introduce the instruments associated with in-situ TEM including the environmental TEM, heating, illumination, biasing, straining devices, and irradiation capabilities. Then, typical applications of these various in-situ TEM capabilities will be discussed. Finally, we will summarize the shortcomings and envision the future of in-situ TEM technologies especially those for the study of catalysis.